Elevation of ganglioside degradation pathway drives GM2 and GM3 within amyloid plaques in a transgenic mouse model of Alzheimer's disease - Wenxuan Wang; Sarah J. Myers; Nikita Ollen-Bittle; Shawn N. Whitehead (Neurobiology of Disease, 2025)
Alzheimer's disease (AD) is a progressive neurodegenerative disease that accounts for two-thirds of all dementia cases, and age is the strongest risk factor. In addition to the amyloid hypothesis, lipid dysregulation is now recognized as a core component of AD pathology. Gangliosides are a class of membrane lipids of the glycosphingolipid family and are enriched in the central nervous system (CNS). Ganglioside dysregulation has been implicated in various neurodegenerative diseases, including AD, but the spatial distribution of ganglioside dysregulation with respect to amyloid-beta (Aβ) deposition is not well understood. To address this gap, matrix-assisted laser desorption/ionization (MALDI) mass spectrometry imaging (MSI) was employed to investigate the age-dependent expression profiles of the A-series ganglioside species GD1a, GM1, GM2, and GM3 in the APP/PS1 transgenic mouse model of AD in which age-dependent amyloid-beta (Aβ) plaques develop. This study utilized a dual-resolution approach in combination with whole-brain imaging for comprehensive detection of ganglioside expression across neuroanatomical regions via high-resolution imaging of the cerebral cortex and hippocampus to investigate plaque-associated ganglioside alterations. The results revealed age-dependent changes in the complex gangliosides GM1 and GD1a across white and gray matter regions in both wildtype and APP/PS1 mice. Significantly greater levels of simple gangliosides GM2 and GM3 were observed in the cortex and dentate gyrus of the hippocampus in transgenic mice at 12 and 18 m than in age-matched controls. The accumulation of GM3 colocalized with Aβ plaques in aged APP/PS1 mice and correlated with Hexa gene expression, suggesting that ganglioside degradation is a mechanism for the accumulation of GM3. This work is the first to demonstrate that age-related ganglioside dysregulation is spatiotemporally associated with Aβ plaques using sophisticated MSI and reveals novel mechanistic insights into lipid regulation in AD.